Teaching as a Professionalism through Teachers’ Perspective - Özdemir, Tuncay Yavuz; Demirkol, Murat; Polat, Hakan (My University, 2019)
The aim of this study is to evaluate teacher professionalism within the framework of teachers'opinions. For this purpose, 45 teachers working at different educational levels and different types(primary, middle and high school) schools in a city located in eastern part of Turkey were includedas participants. The data were collected through interviews and the data were analyzed through thecontent analysis method. The participants with sufficient professional and personal developmentlevel stated that they attended graduate education, read books, and followed the innovations toimprove themselves. Also, it was found that teachers should be encouraged and motivated toadvance their development. The biggest obstacle for their development, teachers mentioned schooladministration, parents and students. Teachers suggested that these obstacles must be overcome toincrease teachers’ willingness to advance their professional and personal skills, and in turn, toincrease schools’ achievement levels. Suggestions for future research is also provided.
Keywords: Eğitim; Eğitim Araştırmaları